Digital city in the pandemic era: a new phase of theoretic discourse - Lebedeva Еlena V. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The transformation of theoretical discourse about the digital city, which occurred under the influence of COVID-19 is analysed. Definition of the «digital city», both the main stages of theoretical ideas about the digital city are given. The main vectors of changes in the post-COVID urban environment as well as their social consequences are outlined. The perspectives of scientific research of the digital city in the post-pandemic period conclude the article.